Podejście procesowe we wdrażaniu SIZ - narzędzia modelowania procesów biznesowych - Kamiński, Andrzej; Polak, Przemysław; Wieczorkowski, Jędrzej (Process Approach in MIS Implementation - Tools for Business Process Modeling, 2005)
Process management is of great importance in modem business. Process reorganization usually implies utilization of information technology. Therefore business process modeling tools are widely used in implementation of management information systems. A review of such tools shows their complexity and maturity in an area of organizational processes, whereas abilities to model and optimize interorganizational processes are limited.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 278-287